2014
DOI: 10.4103/2152-7806.147414
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Neurocytoma: Dilemma in diagnosis and management

Abstract: Background:Central neurocytoma is an uncommon benign tumor of the central nervous system. A section of these tumors have unusual aggressiveness and are termed as “atypical central neurocytomas,” the definition of which is debated. Many studies in the available literature define them as tumors with elevated MIB-1 labeling index (MIB-1 LI) >2%, while some associate them with higher values of MIB-1 LI or those with histological atypical features. Newer parameters also have been identified and correlated with MIB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…Some studies' findings have shown that the proliferative potential of CN may significantly affect patients' prognoses ( 34 , 35 ). Although previous studies' findings have suggested that atypical relatively CNs are associated with shorter OS and PFS intervals ( 4 , 18 , 21 , 22 ), the results from this study showed that there were no differences between the atypical CN group and the typical CN group regarding the OS and PFS durations, and no craniospinal dissemination occurred. In addition, complete tumor resection could prolong OS and control local recurrences in patients with atypical CN.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Some studies' findings have shown that the proliferative potential of CN may significantly affect patients' prognoses ( 34 , 35 ). Although previous studies' findings have suggested that atypical relatively CNs are associated with shorter OS and PFS intervals ( 4 , 18 , 21 , 22 ), the results from this study showed that there were no differences between the atypical CN group and the typical CN group regarding the OS and PFS durations, and no craniospinal dissemination occurred. In addition, complete tumor resection could prolong OS and control local recurrences in patients with atypical CN.…”
Section: Discussioncontrasting
confidence: 99%
“…CN is a rare primary intracranial tumor that is classified as a WHO grade II tumor. However, about 25.0% of these tumors are atypical CNs, which may be more aggressive (1,14,18,21,22). CN treatment includes surgical resection and radiotherapy (15).…”
Section: Discussionmentioning
confidence: 99%
“…MIB-1 (Ki-67) labeling index has been demonstrated to be the most important marker of potentially malignant behavior in CN [ 4 56 57 58 59 60 61 62 63 64 ]. CN is considered atypical if the MIB-1 (Ki-67) labeling index is greater than or equal to 2% [ 4 57 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Söylemezoglu et al [52] found that a MIB-1 LI >2% correlated with microvascular proliferation and suggested that a CN with MIB-1 LI >2% should be termed ‘atypical’ [4]. Atypical CN are also known to spread through the cerebrospinal fluid and metastasize in the ventricles or the spinal cord [100101102103]. …”
Section: Histopathological Analysis and Molecular Pathogenesismentioning
confidence: 99%